An introduction to the methods of decision‐analytic modelling used in economic evaluations for Dermatologists. (27th June 2019) - McManus, E.; Sach, T.H.; Levell, N.J.
Abstract: Economic evaluations are used to identify which health treatments or preventions offer the most effective use of resources, or value for money. This is achieved by identifying, measuring and valuing the inputs and outcomes of alternative interventions. These evaluations are often conducted alongside clinical trials; however, these trials may end before the outcomes of economic interest have been observed and measured. An alternative to within trial economic evaluation is to use decision modelling, which can model the cost‐effectiveness of interventions over an extended time period. This paper aims to provide an overview for clinicians of the different modelling techniques used within health economic evaluations and to introduce methods for critical appraisal. The most common modelling approaches, and their associated strengths and weaknesses, were discussed. Alongside this, practical examples specific to dermatology were given. These examples include studies where the model chosen or the methods used may not have been the most appropriate. Methods for critical appraisal were also highlighted. Common modelling approaches include Decision Trees, Markov Cohort, extensions to the Markov model (Monte Carlo Simulation) and Discrete Event Simulation models. Items of the Philips Checklist were discussed in the context of performing critical appraisal. Health economic decision models are multi‐faceted and can often be complex. Full critical appraisal requires clinicians' unique knowledge, which is complementary to the knowledge of health economists.